1998
DOI: 10.1093/carcin/19.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Frequent reduction of gap junctional intercellular communication and connexin43 expression in human and mouse lung carcinoma cells

Abstract: The reduced gap junctional intercellular communication (GJIC) and gap junction protein (connexin) expression that have been noted in many neoplastic cell types may contribute to the neoplastic phenotype. We assessed GJIC (by fluorescent dye micro-injection) and connexin expression (by Northern blotting, Western blotting and immunohistochemistry) in five mouse and 17 human lung carcinoma cell lines; both measures were lower in neoplastic cells compared to non-transformed lung epithelial cells. Other connexins w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 47 publications
7
57
0
Order By: Relevance
“…38,40 The stably expressing HSV-TK and the parental cell lines grow as a suspension cells in vitro and as expected, no 'bystander effect' could be 38 To increase the efficacy of suicide gene therapy for SCLC, it may therefore be beneficial to include an expression system for connexin 43 together with the suicide gene. In addition, several HSV-TK mutants have been generated, which not only increase the sensitivity for GCV many fold, but also increase the 'bystander effect'.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…38,40 The stably expressing HSV-TK and the parental cell lines grow as a suspension cells in vitro and as expected, no 'bystander effect' could be 38 To increase the efficacy of suicide gene therapy for SCLC, it may therefore be beneficial to include an expression system for connexin 43 together with the suicide gene. In addition, several HSV-TK mutants have been generated, which not only increase the sensitivity for GCV many fold, but also increase the 'bystander effect'.…”
Section: Discussionmentioning
confidence: 90%
“…28,29 In addition to the advantage that GCV is a prodrug already approved for human use, the HSV-TK/GCV system displays 'bystander effects' -both locally and immune mediated. 38,39 Traditionally in vitro assays with suicide genes are performed with virally transduced cell lines, where the suicide gene will be expressed in 100% of the cells with an active promoter. However, using cell lines with relative high transfection efficiencies (approx.…”
Section: Discussionmentioning
confidence: 99%
“…In the lung, Cx43 plays a central role in the regulation of intercellular communications and, although particularly expressed by lung fibroblasts, is considered the major connexin functionally connecting airway, alveolar and endothelial cells [37]. A number of studies have shown a reduced expression of connexins, including Cx43 in some cancers and a subsequent reduction of intercellular communication [38]. The concept of considering both cancer and IPF to share mechanisms closely related to wound healing is also sustained by the involvement of Cx43 in the reparative process that takes place during wound healing.…”
Section: Altered Cell-cell Communicationsmentioning
confidence: 99%
“…For instance, tobacco smoke condensates contain substances with the capacity to inhibit gap junctional communication (123,177,183,184,236,237). Cell lines derived from lung tumors are also frequently not coupled through gap junctions, which can be due to a lack of connexin expression or due to constitutively closed gap junction channels (43,233,234). However, not all correlations of changes in connexin expression with tumorigenesis are significant, since reports that Cx37 mutations might be associated with lung cancer (178) were later found to reflect allelic variability in the human Cx37 gene (150).…”
Section: Open and Shut: Gating Connexin Channels And Regulation Of Cementioning
confidence: 99%